WARS2 mutations cause dopa-responsive early-onset parkinsonism and progressive myoclonus ataxia. (January 2022) - Skorvanek, Matej; Rektorova, Irena; Mandemakers, Wim; Wagner, Matias; Steinfeld, Robert; Orec, Laura; Han, Vladimir; Pavelekova, Petra; Lackova, Alexandra; Kulcsarova, Kristina; Ostrozovicova, Miriam; Gdovinova, Zuzana; et al.
Abstract: Introduction: Sixteen subjects with biallelic WARS2 variants encoding the tryptophanyl mitochondrial aminoacyl-tRNA synthetase, presenting with a neonatal- or infantile-onset mitochondrial disease, have been reported to date. Here we present six novel cases with WARS2 -related diseases and expand the spectrum to later onset phenotypes including dopa-responsive early-onset parkinsonism and progressive myoclonus-ataxia. Methods: Six individuals from four families underwent whole-exome sequencing within research and diagnostic settings. Following the identification of a genetic defect, in-depth phenotyping and protein expression studies were performed. Results: A relatively common (gnomAD MAF = 0.0033) pathogenic p.(Trp13Gly) missense variant in WARS2 was detected in trans in all six affected individuals in combination with different pathogenic alleles (exon 2 deletion in family 1; p.(Leu100del) in family 2; p.(Gly50Asp) in family 3; and p.(Glu208*) in family 4). Two subjects presented with action tremor around age 10–12 years and developed tremor-dominant parkinsonism with prominent neuropsychiatric features later in their 20s. Two subjects presented with a progressive myoclonus-ataxia dominant phenotype. One subject presented with spasticity, choreo-dystonia, myoclonus, and speech problems. One subject presented with speech problems, ataxia, and tremor. Western blotting analyses in patient‐derived fibroblasts showed a markedly decreased expression of the full‐length WARS2 protein in both subjects carrying p.(Trp13Gly) and an exon-2 deletion in compound heterozygosity. Conclusions: This study expands the spectrum of the disease to later onset phenotypes of early-onset tremor-dominant parkinsonism and progressive myoclonus-ataxia phenotypes. Highlights: Biallelic WARS2 variants may cause early onset levodopa-responsive parkinsonism. Myoclonus may be a presenting and prominent feature of WARS2-related disease. In suspected WARS-related disease relaxing of exome filters may be crucial to prioritize the recurrent p.(Trp13Gly) variant.